2019
DOI: 10.1111/1471-0307.12631
|View full text |Cite
|
Sign up to set email alerts
|

Cactus cladode polysaccharide as cryoprotectant in frozen Paneer (Indian Cottage Cheese)

Abstract: The study investigated the optimisation of freezing conditions for Paneer (Indian cottage cheese) incorporated with cactus cladode polysaccharide as cryoprotectant. The freezing rate of both natural and commercial cryoprotectant-containing samples varied significantly. The optimised (2% natural cryoprotectant) Paneer sample had about 44% moisture content, 14% protein, 16% carbohydrate and 22% fat. Freezing time of optimised Paneer sample packed in metalised polyester was 40 min. The study concluded that Paneer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Paneer, as a very popular heat‐acid coagulated product of milk in India and in many other parts of the world, is a highly rich source of nutrition for good quality protein, fat, vitamins and minerals like calcium and phosphorus (Dey et al, 2020; Kumar, Mishra, Sutariya, Chaudhary, & Rao, 2019). It is used in various culinary dishes and snack items throughout the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%
“…Paneer, as a very popular heat‐acid coagulated product of milk in India and in many other parts of the world, is a highly rich source of nutrition for good quality protein, fat, vitamins and minerals like calcium and phosphorus (Dey et al, 2020; Kumar, Mishra, Sutariya, Chaudhary, & Rao, 2019). It is used in various culinary dishes and snack items throughout the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, SHP-3 and SHP-2 contain many smaller molecular weight polysaccharide molecules. The functional sites or active functional groups might be more likely to contact with free radicals or ferrous ions in an aqueous solution and thus show better antioxidant capacity ( 71 , 72 ). The natural polysaccharides of sesame seed hull have the potential to be used as an antioxidant.…”
Section: Resultsmentioning
confidence: 99%
“…Trehalose, xylomannan, and so on, can also exhibit cryoprotective effects and minimize texture changes (Gao et al, 2019;Jittinandana et al, 2005;Kawahara et al, 2016). Dey et al (2020) observed evident changes in textural characteristics, including hardness, adhesiveness, springiness, and chewiness, in the investigated products, and the freezing process was faster when 2% cactus polysaccharide was added to the raw materials during the stirring stage. Gao et al (2019) found that soybean polysaccharides (SPSs) could inhibit decreases in myosin heavy chain concentration and reduce protein degradation after liquid nitrogen freezing.…”
Section: Saccharidesmentioning
confidence: 89%
“…Dey et al. (2020) observed evident changes in textural characteristics, including hardness, adhesiveness, springiness, and chewiness, in the investigated products, and the freezing process was faster when 2% cactus polysaccharide was added to the raw materials during the stirring stage. Gao et al.…”
Section: Approaches For Controlling Ice Crystal Growthmentioning
confidence: 94%